(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Wireless Sensor Network (WSN) is the network of finite potential observing gadgets called sensors. The resource constraint behavior of WSN entails diverse problems in its motif and performance that reduces its execution. Wireless sensor network be unlike to other networks in phrase of accession of aggregation of energy, because at the time of sensors observing and sending the observed data to other sensors, which are covered by the network, a reasonable amount of energy gets reduced. So to overcome this, several routing, potentially organized and data broadcasting protocols are particularly constructed, in which energy devouring is an important design issue that conserves the durability of the network, thereby the lifetime of WSN gets increased. Hierarchical routing protocols which follows an approach of clustering such as Low Energy Adaptive Clustering Hierarchy (LEACH), Stable Election Protocol (SEP), Distributed Energy Efficient Clustering (DEEC) and Threshold Sensitive Energy Efficient Networks (TEEN) are well known for the purpose of keeping up the energy effective. Here we compare these four protocols in phrase of number of nodes dead, packet delivery ratio, number of nodes alive and packets delivered to cluster heads. Keywords: WSN; packet delivery ratio; energy efficiency; hierarchical routing, LEACH; DEEC; TEEN; SEP